2017
DOI: 10.1039/c6nr07989j
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-core NLO-phores: a combined experimental and theoretical approach to the two-photon absorption and two-photon excited emission properties of small-ligated silver nanoclusters

Abstract: We report a combined experimental and theoretical study of the two-photon absorption and excited emission properties of monodisperse ligand stabilized Ag, Ag and Ag nanoclusters in aqueous solutions. The nanoclusters were synthesized using a cyclic reduction under oxidative conditions and separated by vertical gel electrophoresis. The two-photon absorption cross-sections of these protected noble metal nanoclusters measured within the biologically attractive 750-900 nm window are several orders of magnitude lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…Such a difference between emission resulting from absorption of one or two photons was already reported on DNA‐protected and thiolate‐protected silver clusters . This behavior might be accounted for the different nature of the metal‐to‐metal excitations within the gold cluster core (blue emission) and the ligand‐metal and ligand‐metal‐metal charge transfer excitations (red emission) …”
Section: Figurementioning
confidence: 50%
See 3 more Smart Citations
“…Such a difference between emission resulting from absorption of one or two photons was already reported on DNA‐protected and thiolate‐protected silver clusters . This behavior might be accounted for the different nature of the metal‐to‐metal excitations within the gold cluster core (blue emission) and the ligand‐metal and ligand‐metal‐metal charge transfer excitations (red emission) …”
Section: Figurementioning
confidence: 50%
“…We have described in a previous experimental and theoretical investigation how to improve two‐photon absorption (TPA) properties in such quantum nanoclusters, through the concept of “ligand‐core” NLO‐phores . The structure of the metallic core, its charge and symmetry (influencing the NLO cross sections), and the ligands stabilizing the core play major roles in TPA efficiencies . However, the main conclusion so far is that liganded silver and gold quantum clusters are excellent two‐photon absorbers but are rather poor two‐photon excited emitters .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Our investigation on ligand protected silver and gold clusters [8][9][10][11][12][13][14][15] has shown that the structure of the metal atom core, its charge and symmetry, dramatically influence the NLO cross-sections and the core stabilizing ligands play a key role in NLO efficiencies. We coined this new class of NLO materials : "Ligand-Core" NLO-phores 16,17 .…”
Section: Introductionmentioning
confidence: 99%